Synthesis of gold square-like plates from ultrathin gold square sheets : the evolution of structure phase and shape - Huang, Xiao (2014)
It's hip to be square: Gold square-like plates exhibit alternating hexagonal close-packed (hcp, see picture, yellow) and face-centered cubic (fcc, red) structures in the center and defect-free fcc structures at one pair of the opposite thick edges. They can be synthesized from Au square sheets in a secondary growth process. For the first time, the hcp-to-fcc phase transformation associated with shape variation in Au nanostructures is demonstrated.